2021
DOI: 10.3390/md19070354
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9 and IL-1β as Targets for Diatoxanthin and Related Microalgal Pigments: Potential Chemopreventive and Photoprotective Agents

Abstract: Photochemoprevention can be a valuable approach to counteract the damaging effects of environmental stressors (e.g., UV radiations) on the skin. Pigments are bioactive molecules, greatly attractive for biotechnological purposes, and with promising applications for human health. In this context, marine microalgae are a valuable alternative and eco-sustainable source of pigments that still need to be taken advantage of. In this study, a comparative in vitro photochemopreventive effects of twenty marine pigments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Diatoxanthin is an exclusively aquatic microalgal xanthophyll with a (photo-)protective role [ 27 , 28 , 53 ]. Recent findings highlighted its outstanding bioactivity, with marked antioxidant, anti-inflammatory, and chemopreventive properties ([ 27 , 33 ] unpublished data). Interestingly, Dt can induce ferroptosis in cancer cell lines [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Diatoxanthin is an exclusively aquatic microalgal xanthophyll with a (photo-)protective role [ 27 , 28 , 53 ]. Recent findings highlighted its outstanding bioactivity, with marked antioxidant, anti-inflammatory, and chemopreventive properties ([ 27 , 33 ] unpublished data). Interestingly, Dt can induce ferroptosis in cancer cell lines [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dt is eligible as a preventive/therapeutic agent against SARS-CoV-2 infection, cytokine storm consequences at the multiorgan level, and the long-term effects of infection due to the high levels of inflammatory markers in the blood [ 56 ]. A recent in vitro study highlighted that Dt displays antioxidant activity, and exerts an anti-inflammatory role [ 27 ]. Here, it is shown that Dt inhibits IL-6 release in lung cells exposed to the spike glycoprotein, and increases the IL-10 expression, providing an immunomodulatory signaling role.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations